SCIENTIFIC MISSION OF THE RUSSIAN STATE UNIVERSITY FOR THE HUMANITIES - Olga V. Pavlenko (Высшее образование в России)
The article considers the RSUH experience in its scientific activities. The strategic development of the University is aimed at satisfying the needs and demands of the Russian society and Russian state, along with providing the interdisciplinary innovative approaches which are gaining their strength in the world humanitarian knowledge. In other words, the RSUH mission is being realized at such levels as: 1) intercollegiate; 2) in the system of civil and public landmarks; 3) within the humanitarian contexts of Russian and world science. The author presents the model of the RSUH scientific efficiency which includes three groups of tasks. The first one is that of institutional tasks aimed at building an effective scientific structure and installing a qualified profile of a research scientist, along with providing suitable conditions for the faculty to make their scientific research. The second one deals with the interdisciplinary projects and international research. The third extends the RSUH educational mission ofpreserving intellectual traditions and historical memory, as well as reinforcing the value landmarks of Russia and the achievements of its culture and science.